Accuracy of VES-13 in a geriatric outpatient clinic - Duarte, Meirelayne Borges (2023)
This study aims to assess the accuracy of the Vulnerable Elders Survey (VES-13) in a geriatric reference center. This is a cross-sectional study with a convenience sample of older adults (? 60 years) in a geriatric outpatient clinic. The VES-13 score, applied by the researchers, was compared with the strata of the Clinical Functional Classification (CCF), performed by the assistant teams. After descriptive analysis of the variables, the accuracy of the VES-13 was calculated at several cutoff points. A group of 110 individuals were evaluated, aged between 62 and 99 years, with an average of 77.6 (±8.5) years and female predominance (75.5%). Frailty was present in 75.5% of the sample (CCF ? 6) and associated with females by VES-13 (PR = 2.28; 95% CI: 1.24-4.14), but not by CCF (PR = 1.02; 95% CI: 0.79-1.32). Reduced cutoff points showed high sensitivity, higher at score ? 2 (96.4%). The VES-13 score ? 7 obtained the best balance between sensitivity and specificity (63.86% and 59.26%, respectively). The positive predictive value (PPV) was approximately 80% at all cutoffs, possibly due to the high prevalence of frailty in the sample. In conclusion, the accuracy of the VES-13 to identify robust older people (VES-13 ? 2), who can be accompanied exclusively in primary health care (PHC), and fragile older people (VES-13 ? 7), who must be referred to specialized care, is reiterated. The intermediate subgroup (VES-13 between 3 and 6), needs additional assessment to better define their condition, thus configuring a hierarchical comprehensive strategy of health care for older adults.